The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1093/jac/dkn292
|View full text |Cite
|
Sign up to set email alerts
|

Adverse cutaneous reactions associated with the newest antiretroviral drugs in patients with human immunodeficiency virus infection

Abstract: HIV-infected patients have a higher risk of developing cutaneous reactions than the general population, which has a significant impact on patients' current and future care options. The severity of cutaneous adverse reactions varies greatly, and some may be difficult to manage. HIV-infected patients just at the beginning of antiretroviral treatment can frequently show a wide variety of adverse drug effects such as drug rashes, hyperpigmentation, hair loss, hypersensitivity reactions, injection site reaction, ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 77 publications
0
74
0
3
Order By: Relevance
“…Differentiating between adverse consequences of HIV infection and toxicities of drugs used in its management may be challenging. However, following the use of a combination of ARV drugs, some distinct adverse drug events have been reported as case reports [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Differentiating between adverse consequences of HIV infection and toxicities of drugs used in its management may be challenging. However, following the use of a combination of ARV drugs, some distinct adverse drug events have been reported as case reports [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…9 We report a case of severe cutaneous reaction to darunavir/r and a successful desensitization protocol, as described previously. 12,13 The patient was a 41-year-old female, known to be HIV infected for 18 years. Her drug history contained double nucleoside reverse transcriptase inhibitors (NRTIs; zidovudine [ZDV] and zalcitabine [ddC]), combinations of different NRTIs with indinavir (IDV) and later nelfinavir (NFV).…”
mentioning
confidence: 99%
“…Therefore, it is necessary to develop and get approval of novel antiretrovirals as soon as possible in order to avoid these cutaneous adverse reactions. 7 Our study showed that the major regimen induced dermatological complications presenting in our study set up included rashes, itching, SJS, pigmentation of nails, skin hyper pigmentation respectively. The morbilliform eruption, often referred to as a maculopapular rash, is the most common type of reaction after treatment.…”
Section: Discussionmentioning
confidence: 56%